2016
DOI: 10.14393/bj-v32n5a2016-32754
|View full text |Cite
|
Sign up to set email alerts
|

Drying and storage of corn grains for ethanol production in Brazil

Abstract: ABSTRACT:The aim of the present research was to evaluate the effects of drying air temperature and storage conditions used in Brazil on the quality of corn grains (Zea mays L.) for ethanol production. The experiment was set up in a completely randomized design in a (3x2x2) factorial arrangement (drying air temperatures of 80, 100 and 120 ºC vs. ambient storage conditions of 23 ºC / 60% RH and cooled to 10 ºC / 40% RH vs. storage time of zero and six months). The corn grains were harvested with a water content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
5
0
2
Order By: Relevance
“…Aeration of the stored grain mass did not significantly reduce the grain mass temperature (0.5 to 1 °C) which (Cardoso et al, 2012;Quirino et al, 2013;Coradi et al, 2016b;Nascimento & Queiroz, 2016). In these conditions, it was observed that the grain deterioration process increased as a function of the water content change after equilibration with the air temperature and relative humidity ( Table 3).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Aeration of the stored grain mass did not significantly reduce the grain mass temperature (0.5 to 1 °C) which (Cardoso et al, 2012;Quirino et al, 2013;Coradi et al, 2016b;Nascimento & Queiroz, 2016). In these conditions, it was observed that the grain deterioration process increased as a function of the water content change after equilibration with the air temperature and relative humidity ( Table 3).…”
Section: Resultsmentioning
confidence: 92%
“…The losses of products during storage mean financial losses for the product holder. Grains can suffer damage during storage period due to external or inherent factors affecting the grain mass which are: physical (humidity and temperature), chemical (oxygen availability), and biological (rodents, insects, fungi, and bacteria) factors (Lopes et al, 2010;Barbosa et al, 2012;Rigo et al, 2012;Quirino et al, 2013;Coradi et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%
“…According to the authors, this is because the source of H 2 results from water vapor from root respiration by the action of ferredoxin containing sulfur (Vitti et al, 2015).Since gypsum provides a greater absorption of nutrients and water by the plant (Souza and Lobato, 2004), the increase in the physical properties of the grains in function of the increase in gypsum doses is attributed to a greater increase in water content in relation to photoassimilates. This is proven by porosity showing an increase (0.41%) higher than the weight of 1,000 grains (0.29%), which is linked to a decrease in the associated with the decrease of water levels, lead to reductions in length, width, thickness, volume, circularity and roundness of corn grains (Coradi et al, 2016). Since there was variability for gypsum doses, the path analysis revealed a severe multicollinearity for the inverse matrix of independent variables (determinant of the matrix X'X = 1.36 x 10 -4…”
Section: Resultsmentioning
confidence: 96%
“…A deterioração da massa de grãos armazenados é o resultado da interação entre variáveis físicas (temperatura e umidade); químicas (disponibilidade de oxigênio no ar intergranular) e biológicas (respiração e microrganismos). O percentual de degradação dos grãos é diretamente proporcional ao aumento e sinergismo do efeito destas variáveis (CHULZE, 2010;QUIRINO et al, 2013;CORADI et al, 2016). A umidade e temperatura são as variáveis que mais influenciam a taxa de degradação (CORADI et al, 2015).…”
Section: Introductionunclassified